Response of the Coccinellidae community within sustainable vineyards to the surrounding landscape - Taranto, Luisa (2022)
The family Coccinellidae (Coleoptera) includes important predatory natural enemies in agricultural crops. To survive, this group uses different occurring resources across the landscape; therefore, the landscape can influence the Coccinellidae community in agroecosystems. In this context, this work aims to evaluate the response of the Coccinellidae community to the landscape context within a gradient of distances from vineyards managed under sustainable production methods. For that, Coccinellidae were sampled in thirty-five vineyards distributed by six wine Protected Designation of Origin (PDO) regions of Portugal, and landscape metrics—composition and configuration—were calculated in a 2000 m, 1500 m, 1000 m, 750 m, and 500 m buffers around the vineyards. Then, Coccinellidae species were identified, and the response of the Coccinellidae to the landscape metrics was analyzed. In total, 326 Coccinellidae from 21 species were collected. The most abundant species were Scymnus apetzi, Scymnus interruptus, Scymnus subvillosus, Coccinella septempunctata, and Stethorus pusillus, which together represented 83.4% of the total collected individuals. Most specimens were concentrated in July and at the vegetation cover. Results from the statistical analysis (Generalized Linear Mixed Models) indicated that the presence of seminatural habitat surrounding the crop may favor Coccinellidae, while habitat fragmentation seems detrimental for them. The potential relevance of the identified Coccinellidae for pest control in vineyards is discussed.